2022
DOI: 10.1002/mame.202200208
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Property–Processing Relations of Short‐Chain Branched Poly(butylene terephthalate) (PBT) with Biobased Comonomers

Abstract: Poly(butylene terephthalate) (PBT) is difficult to foam due to its unfavorable rheological behavior (low melt strength, no strain hardening). In particular, a high expansion and a homogeneous cell morphology are difficult to achieve. This can be altered successfully by addition of multifunctional chain extenders. Chain extenders cause nondefined and rarely understood changes in the polymer architecture usually described as branching. In this contribution, the synthesis of two series of PBT copolyesters with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In previous investigations we were able to gain more insights into the bead fusion mechanism of E-PBT. [34,35] In the temperature range where the molding process takes place (Figure 1), unmodified E-PBT crystallizes faster than CE modified E-PBT as indicated by a cold-crystallization peak. We could show that the incorporation of chain extender significantly increases the steric hindrance, slows down crystallization and reduces cold-crystallization in the fusion temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…In previous investigations we were able to gain more insights into the bead fusion mechanism of E-PBT. [34,35] In the temperature range where the molding process takes place (Figure 1), unmodified E-PBT crystallizes faster than CE modified E-PBT as indicated by a cold-crystallization peak. We could show that the incorporation of chain extender significantly increases the steric hindrance, slows down crystallization and reduces cold-crystallization in the fusion temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous report of our group, dilinoleic derivatives have been successfully demonstrated as comonomers for PBT to introduce short‐chain branching to modify the extensional rheology of PBT in copolyesters. [ 39 ] This resulted in improved bead foaming and fusion of compact parts. Until then, high temperatures and molar masses of PBT together with a multifunctional epoxy‐containing chain extender were necessary to achieve proper foaming and welding of the resulting beads.…”
Section: Introductionmentioning
confidence: 99%
“…The process for extrusion foaming of PBT was developed in the groups of Altstädt and Ruckdäschel. [2,3,39,40,[48][49][50][51][52][53] The foamed beads were analyzed by NMR spectroscopy, density measurements, scanning electron microscopy (SEM), micro-computed tomography (𝜇-CT), and DSC.…”
Section: Introductionmentioning
confidence: 99%
“…The higher melting crystals remain unaffected and maintain the foam structure. So far, investigations of the thermal behavior showed that both described mechanisms cannot be fully valid for E-PBT , as the DSC curves of the single beads show one melting peak. It is assumed (i) that the aforementioned CE influences the crystallization behavior of the beads and that the surface of the beads differs from the core (e.g., higher amorphous fraction, different degrees of cold-crystallization and crystallization rates) (Figure ) and/or (ii) that the CE is not completely consumed during the production of the single beads and is activated by the steam, which allows adhesion by forming chemical bonds.…”
Section: Introductionmentioning
confidence: 99%